Provision of Marketing Services in the Field of Digital Economy - Musayeva Shoira Azimovna,; Fayziev Sardorkhon Sanjarkhonovich. (Research Parks Publishers, 2023)
This article is devoted to identifying the role and improving the quality of marketing in the digital economy as a result of researches on difital transformation. And also offers are presented that can help improve the quality of sevices provided in all sectors of the economy.